The distant type Ia supernova rate - Pain, R; Fabbro, S; Sullivan, M; Ellis, R; Aldering, G; Astier, P; Deustua, SE; Fruchter, A; Goldhaber, G; Goobar, A; Groom, D; Hardin, D; et al. (Institute of Physics Publishing, 2002)
We present a measurement of the rate of distant Type la supernovae derived using four large subsets of data from the Supernova Cosmology Project. Within this fiducial sample, which surveyed about 12 deg2, 38 supernovae were detected at redshifts 0.25-0.85. In a spatially flat cosmological model consistent with the results obtained by the Supernova Cosmology Project, we derive a rest-frame Type la supernova rate at a mean redshift z ≃ 0.55 of 1.53-0.25-0.31-0.28-0.32 × 10-4 h 3 Mpc-3 yr-1 or 0.58-0.09-0.09-0.10-0.10 h2 SNu (1 SNu = 1 supernova per century per 1010 LB⊙), where the first uncertainty is statistical and the second includes systematic effects. The dependence of the rate on the assumed cosmological parameters is studied and the redshift dependence of the rate per unit comoving volume is contrasted with local estimates in the context of possible cosmic star formation histories and progenitor models.